Pengaruh Media Cerita Bergambar Berbasis Cerita Rakyat terhadap Kemampuan Membaca Pemahaman Siswa Kelas III Sekolah Dasar Gugus III Pagutan Tahun Ajaran 2025/2026 - Yulia Dewi Indriani; Syaiful Musaddat; Setiani Novitasari (Mataram University, 2026)
This study aims to determine the effect of folklore-based picture story media on the reading comprehension of third-grade students of Elementary School Cluster III Pagutan in the 2025/2026 academic year. This study uses a quantitative approach with a quasi-experimental design. The research sample consisted of third-grade students of SDN 2 Sangkawana as the experimental class and third-grade students of SDN 1 Tunjang as the control class. The data collection technique used a reading comprehension ability test in the form of a pretest and posttest. Data analysis was carried out using the Shappiro Wilk normality test, Levene test homogeneity test, Mann-Whitney U Test, and effect size test. The results showed that the average posttest score of the experimental class was 71.29, higher than the control class at 53.23. The results of the hypothesis test obtained an Asymp. Sig. (2-tailed) value of 0.008 <0.05, which indicates that there is a significant effect of the use of folklore-based picture story media on students' reading comprehension. Illustrated story media helps students understand the content of reading through visual illustrations and stories that are close to students' lives.